On the origin of BAG(3) and its consequences for an expansion of BAG3's role in protein homeostasis. Issue 1 (4th May 2021) - Baeken, Marius W.; Behl, Christian
Abstract: The B‐cell CLL 2‐associated athanogene (BAG) protein family in general and BAG3, in particular, are pivotal elements of cellular protein homeostasis, with BAG3 playing a major role in macroautophagy. In particular,  in the contexts of senescence and degeneration, BAG3 has exhibited an essential role often related to its capabilities to organize and remove aggregated proteins. Exciting studies in different species ranging from human, murine, zebrafish, and plant samples have delivered vital insights into BAG3s' (and other BAG proteins') functions and their regulations. However, so far no studies have addressed neither BAG3's evolution nor its phylogenetic position in the BAG family. Abstract : In our here presented research, we were able to identify possible and highly conserved LC3 interacting region (LIR) motifs within the protein structure of BAG3. These revelations may cast a new light on BAG3's role in proteostasis and autophagy, independent of other receptor and adaptor proteins.